Pemanfaatan Tepung Biji Nangka dan Sale Pisang Ambon dalam Pembuatan Snack Bar - Tuah Hamonangan Simanjorang; Vonny Setiaries Johan; Rahmayuni Rahmayuni (JURNAL AGROINDUSTRI HALAL, 2020)
The purpose of this research was to obtain snack bar with the optimum sensory and chemical characteristics.  This research used a completely randomized design with five treatments and three replications.  Data were statistically analyzed using analysis of variance (ANOVA) and followed by Duncan’s New Multiple Range Test (DNMRT) at level 5%.  The treatments performed were the differential ratio between jackfruit seed flour and dried slice of ambon banana, namely BNP1 (80:20), BNP2 (70:30), BNP3 (60:40), BNP4 (50:50) and BNP5 (40:60). The result showed that each treatment significantly affected all the observational parameters both chemically and sensory. Jackfruit seed flour : dried slice of ambon banana (40:60) is the optimum treatment which is preffered hedonically with a description of brownish yellow color, banana aroma, banana flavored and having soft level of hardness, having 23.98% moisture content, 2.05% ash content, 11.61% fat content, 5.86% protein content, 56.50% carbohydrate content and 0.88% crude fiber content.Keywords: snack bar, jackfruit seed flour, dried slice of ambon banana